Applied radiological anatomy - Butler, Paul, 1954 June 4.; Mitchell, Adam W. M.; Ellis, Harold, 1926- (Cambridge ; New York : Cambridge University Press, 2012)
"This expanded new, full colour edition of the classic Applied Radiological Anatomy is an exhaustive yet practical imaging resource of every organ system using all diagnostic modalities. Every illustration has been replaced, providing the most accurate and up-to-date radiographic scans available. Features of the second edition: Completely new radiographic images throughout, giving the best possible anatomic examples currently available Both normal anatomy and normal variants shown Numerous colour line illustrations of key anatomy to aid interpretation of scans Concise text and numerous bullet-lists enhance the images and enable quick assimilation of key anatomic features Every imaging modality included Edited and written by a team of radiologists with a wealth of diagnostic experience and teaching expertise, and lavishly illustrated with over 1,000 completely new, state-of-the-art images, Applied Radiological Anatomy, second edition, is an essential purchase for radiologists at any stage of their career"--
"Introduction and imaging methods Computed tomography (CT) and magnetic resonance imaging (MRI) are the mainstays of cerebral imaging. Skull radiography now plays very little part in diagnosis, being largely replaced by multislice CT.Non- or minimally invasive angiography performed using CT, (CT angiography), or MRI, (magnetic resonance angiography), has resulted in invasive catheter angiography being reserved for a few special diagnostic indications or as part of an interventional, (therapeutic), procedure. Anatomical detail is far better displayed by MRI than by CT, although both are valuable in clinical practice"--
Machine generated contents note: Preface; Part I. Central Nervous System: 1. The skull and brain Kieran Hogarth, Josef Jarosz and Paul Butler; 2. Orbit and visual pathway Indran Davagnanam and Jonathan Hart; 3. Ear and auditory pathway Tim Beale and Simon Morley; 4. Extracranial head and neck Tim Beale; 5. The vertebral column and spinal cord Asif Saifuddin; Part II. Thorax and Abdomen: 6. Chest and mediastinum Sheila Rankin; 7. Heart and great vessels Simon Padley and Narayan Karunanithy; 8. Breast Steve Allan; 9. The anterior abdominal wall and peritoneum Nishat Bharwani and Rodney Reznek; 10. Abdomen and retroperitoneum Aslam Sohaib and Navin Ramachandran; 11. The gastrointestinal tract Nasir Khan; 12. The urogenital tract Uday Patel and Hema Verma; 13. The male pelvis Nevin T. Wijisekera and Uday Patel; 14. The female pelvis Catriona Davies; Part III. Upper and Lower Limb: 15. Upper limb Gajan Rajeswaran and Justin Lee; 16. Lower limb Gonzalo Ansede; Part IV. Obstetrical Imaging: 17. Obstetrical imaging Ian Suchet; Index.
Includes bibliographical references and index.
Keywords: Radiography, Medical; Human anatomy; Human anatomy -- Atlases